2003
DOI: 10.1016/s0003-682x(03)00022-7
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of an isodynamic transducer for use in active acoustic materials

Abstract: Active control of the acoustic impedance of walls in rooms allows fine control of the reverberation in auditoria. Such active materials may use locally reacting cells comprising a transducer connected to an electronic control circuit. In this paper, a simple feedback circuit based on a linear combination of the pressure at the transducer diaphragm and the velocity of the diaphragm is presented. We then discuss the desired characteristics of a transducer dedicated to our application, and show that the isodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…One can observe that, with the chosen electric network, the coefficients of s 2 and s 0 in the denominator of the synthesized acoustic admittance Y s,3a (s) are lower than in the passive case [see Eq. (19)]. This is in accordance with the objective of lowering the equivalent mass and increasing the equivalent compliance of the loudspeaker in order to extend the bandwidth of the control.…”
Section: Case 3: Direct Impedance Controlsupporting
confidence: 65%
See 1 more Smart Citation
“…One can observe that, with the chosen electric network, the coefficients of s 2 and s 0 in the denominator of the synthesized acoustic admittance Y s,3a (s) are lower than in the passive case [see Eq. (19)]. This is in accordance with the objective of lowering the equivalent mass and increasing the equivalent compliance of the loudspeaker in order to extend the bandwidth of the control.…”
Section: Case 3: Direct Impedance Controlsupporting
confidence: 65%
“…Employing "negative" resistances (through negative impedance converters) further varies the acoustic impedance of the device. 15 The performances of shunt loudspeakers can also be enhanced with an "hybrid feedback," 18,19 in which the acoustic impedance of a loudspeaker is broadly modified by connecting a negative resistance in series with a sound pressure-feedback. Since the negative impedance realizes motional feedback, 13 the acoustic performances obtained with hybrid feedback are similar to the above-mentioned direct impedance control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The use of basic active noise control for the reduction of wall reflections is an old topic, proposed several decades ago for underwater acoustics [6] and audio use [7]. This concept has then been thoroughly validated and improvements have been proposed [8,9,10,11,12,13]. Related work is still in progress, the main concerns being to implement a practical sensing method and widen the application range.…”
Section: Introductionmentioning
confidence: 99%
“…Cheung (2010) studied shunted loudspeaker as Helmholtz resonator to reflect low-frequency duct noise. Lissek and Meynial (2003) and Lissek et al (2009), who were among the first to develop such shunt circuit techniques, used a shunted loudspeaker to control wall acoustic impedance. Their further work (Lissek et al, 2011;Boulandet and Lissek, 2010) reported good low-frequency absorption in a relative narrow frequency-band, which is achieved by resonance of shunted loudspeaker.…”
Section: Introductionmentioning
confidence: 99%